Effectiveness of Correctional Institution (BAPAS) Guidance Towards The Fulfillment Of Children's Rights as Murder Perpetrators (Decision Number 19/Pid.Sus-Anak/2022/Pn Dps) - Gorda, AAA Ngurah Tini Rusmini; Lestari, Dewi Novita; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Children need special attention and protection to support optimal physical, mental, and social growth and development. In the legal context, handling children involved in criminal acts, including murder, requires a different approach from adult perpetrators. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) regulates special treatment for children in conflict with the law, with the Correctional Center (Bapas) as a strategic institution in protecting children's rights. This study aims to analyze the effectiveness of the Bapas' role in assisting children who have committed the crime of murder, especially in the case of Decision Number 19/Pid.Sus-Anak/2022/PN Dps. The research method used is an empirical design through interviews with judges at the Denpasar District Court, Bapas Class I Denpasar officers, and informants at the Karangasem Class II Juvenile Correctional Institution. The results of the study indicate that Bapas plays a strategic role in providing legal assistance, community research (litmas), and mediation that prioritizes restorative justice-based resolution. This role aims to ensure that children's rights are protected and children are treated fairly without discrimination, in accordance with Article 1 Paragraph (8), Article 3, and Article 64 of the SPPA Law. The effectiveness of assistance is determined by the professionalism of officers, policy support, and synergy with families and communities. This study emphasizes the importance of an approach based on the principle of the best interests of children in ensuring the fulfillment of children's rights during the legal process, while supporting their rehabilitation and social reintegration.